Case study on prediction of remaining methane potential of landfilled municipal solid waste by statistical analysis of waste composition data - Sel, Ilker; Cakmakci, Mehmet; Ozkaya, Bestamin; Altan, H. Suphi (PERGAMON-ELSEVIER SCIENCE LTD, 2016)
Main objective of this study was to develop a statistical model for easier and faster Biochemical Methane Potential (BMP) prediction of landfilled municipal solid waste by analyzing waste composition of excavated samples from 12 sampling points and three waste depths representing different landfilling ages of closed and active sections of a sanitary landfill site located in Istanbul, Turkey. Results of Principal Component Analysis (PCA) were used as a decision support tool to evaluation and describe the waste composition variables. Four principal component were extracted describing 76% of data set variance. The most effective components were determined as PCB, PO, T, D, W, FM, moisture and BMP for the data set. Multiple Linear Regression (MLR) models were built by original compositional data and transformed data to determine differences. It was observed that even residual plots were better for transformed data the R-2 and Adjusted R-2 values were not improved significantly. The best preliminary BMP prediction models consisted of D, W, T and FM waste fractions for both versions of regressions. Adjusted R-2 values of the raw and transformed models were determined as 0.69 and 0.57, respectively. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Waste characterization; Prediction; Methane potential; Multiple linear regression; PRINCIPAL COMPONENT ANALYSIS; NEAR-INFRARED SPECTROSCOPY; PARAMETERS; Engineering; Environmental Sciences & Ecology